ANTHROPOMETRIC WALL CHART OF HEIGHT FOR AGE FOR STUNTED SCREENING IN PRIMARY SCHOOL CHILDREN Anthropometric Wall Chart Tinggi Badan menurut Umur untuk Skrining Stunted pada Anak Sekolah Dasar - Aryani Sudja; Asep Iwan Purnawan; Helmi Rosmalia (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Stunted or short nutritional status is a term that describes a person's nutritional status based on height for age. The prevalence of stunting in school children in Indonesia in 2017 was 27.7%. Children who are stunted have the potential for growth and development disorders, low motor skills, mental and intellectual development disorders, and have lower productivity than normal children of the same age. The purpose of this study was to determine the sensitivity and specificity value of the anthropometric wall chart height for age index for stunting screening in elementary school children. The study design was cross-sectional in four elementary schools in Cimahi City with a total sample of 330 children aged 6 to 12 years. Each child was measured for height twice, using a microtoise tool and anthropometric wall chart. The results of height measurement at a certain age were compared with the 2005 World Health Organization standards. They were declared stunted (short) if the height for age value <-2 standard deviation and declared very short if the height for age value <-3SD. The index value is based on the 2005 WHO standard, which is used as the gold standard in calculating validity. Measurement results using an anthropometric wall chart by looking at the color band shown on the upper border of the child's head. If the head border of the child is on a yellow or red band at a certain age, it means that the child is stunting. The sensitivity value of the anthropometric wall chart is 85.7%, and the specificity value is 87.2%. The anthropometric wall chart can be used for stunted screening in children aged 6-12 years.